Enhanced cloud storage access control scheme based on attribute - De-hua NIU; Jian-feng MA; Zhuo MA; Chen-nan LI; Lei WANG (Tongxin xuebao)
In order to ensure the security of data and privacy in cloud storage, an enhanced cloud storage access control solution based on attribute was proposed. By designing a common set of attributes, attribute-based encryption(ABE) was integrated into XACML (eXtensible access control markup language) framework and the goal to ensure the confidential-ity of sensitive data and to provide fine-grained access control was achieved. Considering the efficiency of ABE is very low when it is used to a large amount of data, symmetric cryptography was used to ensure the confidentiality of the vast amounts of sensitive data while ABE was used to protect the small number of symmetric keys. Experiments show that the scheme can ensure the confidentiality of the data and privacy and its performance is superior to other similar systems.